Le prince et les animaux Une histoire zoologique de la cour de Versailles au siècle des Lumières (1715-1792) - Pieragnoli, Joan (Etudes sur le XVIIIe siècle series, 2021)
The zoological history proposed here, by looking at hunting practices and the management of animal populations that they entailed, attempts to explain the disaffection of Versailles in the 18th century.